2013
DOI: 10.1007/s11356-013-1697-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and removal of polycyclic aromatic hydrocarbons in wastewater treatment processes from coke production plants

Abstract: Identification and removal of polycyclic aromatic hydrocarbons (PAHs) were investigated at two coke plants located in Shaoguan, Guangdong Province of China. Samples of raw coking wastewaters and wastewaters from subunits of a coke production plant were analyzed using gas chromatography-mass spectrometry (GC/MS) to provide a detailed chemical characterization of PAHs. The identification and characterization of PAH isomers was based on a positive match of mass spectral data of sample peaks with those for PAH iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…3 and 4) as compared to those in the sludge treating municipal sewage ) and other industrial wastewaters (Ibarbalz et al 2013) that may be credited to complex nature of CWW as shown in previous literatures (Zhang et al 2013;Zhao et al 2014;Hou et al 2015) and also in this study. Interestingly, bacterial and fungal community compositions in the sludge were in accordance to bioreactor performance removing majority of organic and toxic pollutants.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…3 and 4) as compared to those in the sludge treating municipal sewage ) and other industrial wastewaters (Ibarbalz et al 2013) that may be credited to complex nature of CWW as shown in previous literatures (Zhang et al 2013;Zhao et al 2014;Hou et al 2015) and also in this study. Interestingly, bacterial and fungal community compositions in the sludge were in accordance to bioreactor performance removing majority of organic and toxic pollutants.…”
Section: Discussionsupporting
confidence: 72%
“…In the aerobic sludge, the high abundances of Thiobacillus, Comamonas, Diaphorobacter, Ottowia, and Weeksella (Table S8), which reportedly degrade several phenol and SCN − compounds (Felföldi et al 2010;Beller et al 2006;Klankeo et al 2009;Yuste et al 2000), were in accordance with the significant removal of pollutants in the final effluent. As referred in Table S8, the significant presence of PAHdegrading bacteria like Comamonas (Goyal and Zylstra 1996) and Diaphorobacter (Klankeo et al 2009) indicated the removal of corresponding pollutants in aerobic sludge leading to detoxification of CWW (Zhang et al 2013). The high abundances of NHC-degrading bacteria Brevundimonas, Sphingopyxis, Sphingosinicella Stolz 2009;Baik et al 2013), and Comamonas (Felföldi et al 2010;Zhang et al 2015) also tallied with the complete disappearance of NHCs in the final effluent in this study.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…China contributed to most of the hard coke production in the world and the discharge of coking wastewater in China was over 1.8 × 10 8 t in 2005 (Wei et al 2007;Zhang et al 1998). Hazardous materials, both the inorganic and organic compounds, especially refractory and inhibitory organics, e.g., phenols, polycyclic aromatic hydrocarbons, pyridine, and indole, are found at high concentrations in coking wastewater (Zhang et al 2013). The pollutants in the coking wastewater may affect all aspects of the environment including water, air, and land and exert significant adverse effects on the ecological environment (Han et al 2011), as such the Chinese government has adopted a series of measures to treat and manage coking wastewater, this includes establishing stricter discharge standards of pollutants for coking chemical industry in 2012 (GB16171-2012).…”
Section: Introductionmentioning
confidence: 99%